Agricultural Transformation and Farmers' Expectations: Experimental Evidence from Uganda - Bonan, Jacopo; Kazianga, Harounan; Mendola, Mariapia (The Review of Economics and Statistics, 2025)
Abstract This paper uses the randomized rollout of a national agricultural extension program in Uganda to study subsistence smallholders' decisions to adopt cash oilseed crops and shift to commercial farming. By eliciting yield and price expectations, we examine how beliefs evolve after the intervention and influence adoption decisions. Our findings indicate that technical and market information significantly raises farmers' expectations, leading to an average 15% increase in oilseed adoption. Results highlight the role of information in shaping beliefs and behavior, and suggest that addressing knowledge gaps and belief misperceptions about crop profitability is crucial for improving technology adoption and agricultural transformation.